Situação das propriedades leiteiras na bacia do Alto Paraguai em Mato Grosso : uma análise de gestão estratégica e Balanced Scorecard - Silva, Gladistone Soares Lopes da (2017)
This dissertation addresses the implementation and execution of the organizational and commercial strategy on dairy farms. The problem that guides this research is whether the production structure of milk producers in the Alto Paraguai productive cluster, the commercialization model, and the public policies to promote milk production, meet the conditions for the development of the milk production chain in this cluster? The objective of the research was to identify the socioeconomic profile and the production factors on the dairy farms in order to elaborate the production and commercial strategy for these properties. Field research was carried out on 120 dairy farms located in the cities of Alto Paraguai, Arenápolis, Denise, Nova Olímpia, Santo Afonso and Tangará da Serra in the state of Mato Grosso. The selection of these cities considered previous studies developed by the Federal University of Mato Grosso (UFMT), developed based on the design of Local Productive Arrangements, promoted by the National Bank for Economic and Social Development (BNDES). It is also a productive arrangement registered with the National GTP-APL, supported by the Ministry of Development, Industry and Foreign Trade (MDIC). In order to elaborate the strategy the method used was the balanced scorecard. The analysis of the research data allowed us to identify the performance vectors that guided the strategy elaboration and determine the outcome indicators that were chained in a cause and effect relationship within the perspective of the balanced scorecard. For the communication of the strategy to the workers the strategic map of the balanced scorecard was elaborated. The organization of the strategy for the properties using the Balanced Scorecard system allows a better understanding to all involved in its execution, promoting a cultural change capable of promoting the arrangement of the work of all around the strategic objectives. In the discussion of the results, the lack of structure and planned management is evident in most of the surveyed properties, which results in low productivity and performance of the activity. It was also concluded that the inability of the government to promote local development, generating competitive advantages in the milk production chain, due to the bureaucratic process and the lack of arrangement between the involved agents.